Development of brief cognitive behavioral therapy workshop study protocol for primary care attendees with common mental disorders in Selangor, Malaysia - Sam, Jeng Mun; Ismail, Siti Irma Fadhilah; Tan, Kit-Aun; Mohd-Sidik, Sherina; Osman, Zubaidah Jamil (Malaysian Psychological Association, 2023)
The prevalence of Common Mental Disorders (CMD) in the primary care appears to be high, yet most of the individuals who can benefit from early and evidenced-based psychological approaches are limited. Barriers concerning stigma, lack of access to psychological interventions, high volume of primary care attendees, and poor awareness in mental health are among the factors that contribute to the accessibility of mental health treatments. The paper proposed a study protocol from past literatures’ recommendations to integrate psychological interventions in the primary care setting. Implementation of the brief Cognitive Behavioral Therapy workshop (b-CBT) as the potential approach to address the issues and symptoms of CMD in the primary care clinics using a nonrandomized quasi-experimental study is proposed. The study will use a multivariate analysis of covariance (MANCOVA) to analyze the 84 prospective participants, using purposive sampling. The targeted identification of cognition, behavior and emotions from b-CBT model is expected to be able to address the symptoms relating to CMD. Results will show the potential changes of symptoms measured by Depression, Anxiety, and Stress Scale, 21 items (DASS-21) for three time-points (baseline, post-intervention, and one-month follow-up). The reporting guideline for the paper follows the TREND statement reporting guidelines.